2006
DOI: 10.1086/499044
|View full text |Cite
|
Sign up to set email alerts
|

Response to Antiretroviral Therapy in HIV-Infected Patients Attending a Public, Urban Clinic in Kampala, Uganda

Abstract: Although many HIV-infected people treated in Kampala, Uganda, have advanced HIV disease, the majority of patients who received antiretroviral therapy experienced viral suppression and clinical benefit. Because of the frequent use of nonnucleoside reverse-transcriptase inhibitor-based therapy, the majority of resistance was against this drug class. In resource-limited settings, initiation of therapy with a potent, durable regimen, accompanied by stable drug supplies, will optimize the likelihood of viral suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 21 publications
0
58
1
Order By: Relevance
“…Whereas several publications (Calmy et al, 2006;Spacek et al, 2006;Wester et al, 2005) and recent presentations from large cohorts in Uganda, Kenya and South Africa (Boulle et al, 2006;Forna et al, 2006;Kim et al, 2006) reported on toxicities such as neuropathy and lactic acidosis, lipoatrophy has not been stated as an important problem and this is in clear contrast to our data (van Griensven et al, 2006). There might be a number of possible reasons for this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Whereas several publications (Calmy et al, 2006;Spacek et al, 2006;Wester et al, 2005) and recent presentations from large cohorts in Uganda, Kenya and South Africa (Boulle et al, 2006;Forna et al, 2006;Kim et al, 2006) reported on toxicities such as neuropathy and lactic acidosis, lipoatrophy has not been stated as an important problem and this is in clear contrast to our data (van Griensven et al, 2006). There might be a number of possible reasons for this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…While other cohort data from the IDI [29] and other African centres [3,43-46] have reported excellent 12-month outcomes, this result is likely to have been affected by survival bias. Due to the cross-sectional nature of this study, our results may not account for early losses to follow up (from deaths, etc.)…”
Section: Discussionmentioning
confidence: 80%
“…These observations reflect the relatively low genetic barrier to antiviral drug resistance for NNRTIs, as well as the prolonged plasma half-lives of NNRTIs, which lead to functional monotherapy as NRTI concentrations in plasma decrease. In resource-limited areas, treatment interruptions may be more common because of the relatively high cost of the medications, the difficulty of accessing health care services, and challenges in the distribution and uninterrupted delivery of drug supplies [28].…”
Section: Discussionmentioning
confidence: 99%